THE EFFECTIVENESS OF USING INTERACTIVE WRITING IN TEACHING WRITING - Hidayati Hidayati (Linguistics and ELT Journal, 2015)
This experiment was to evaluate the  effectiveness of using interactive writing  in teaching writing at the second grade students of MTs Al-Raisiyah Sekarbela in Academic year 2014/2015.66 out of 100 students participated during the treatment. This study used quasi-experiment design which comprised two groups as the experiment and the control groups. To obtained the findings, tests were administered before and after the treatment. The results showed the interactive writing strategy was effective to help students improve their writing skill.